Ocular ischemic syndrome; A case report - Benjankar, Manju; Sitaula, Sanjeeta; Karki, Pratap (Nepalese Journal of Ophthalmology, 2019)
Background: Ocular ischemic syndrome is not a common condition so most of these cases are often misdiagnosed or treated as a different entity. Therefore, it is very important for the ophthalmologists to have this condition in mind as a differential so that the patients can be diagnosed and treated as early as possible. A 42 years female presented with painless, progressive diminution of vision in right eye over the period of 1 month. She doesn’t give any history of redness of eyes, fever or trauma. There is no history of diabetes mellitus or hypertension as well. On examination, vision in right and left eyes was 1.78 and 0.30 Log Mar Units respectively. On anterior segment examination, revascularization of iris (1o 4 ‘o’clock hrs) in right eye was noted. On dilated fund us copy, revascularization of disc (1/3rd) was present in right eye. Cotton wool spots blot hemorrhages and micro aneurysms were also noted in right eye. Likewise, attenuation of arteries were noted on both sides. Fund us fluorescent angiography revealed delayed artery covetous and venous phase. Carotid Doppler was done which showed complete occlusion of right common carotid and bilateral internal carotid artery. These findings lead to the diagnosis as ocular ischemic syndrome so she was then referred to the cardiologist who further confirmed that no active intervention was required at present. The patient was planned for right eye pan retinal photocoagulation (PRP) and was completed in 2 sittings and was asked to follow up regularly.Conclusion: Early diagnosis and management is very important for uncommon conditions such as ocular ischemic syndrome to prevent further complications.